Implementação computacional da análise da DTR em reatores ideais e não-ideais - Pasqua, Carlos Catusso Della (2022)
The presence of computational tools has become essential to help in the numerous setbacks that engineers and researchers face in their daily lives, providing reliability and agility in solving highly complex problems. In this way, an incentive is seen in the use of programming languages for the elaboration of computational tools for chemical engineering issues. In the present work, a computational tool was implemented for assisting in the analysis of the residence time distribution (RTD) in non-ideal reactors beyond the calculation of the estimated conversion. By segregation and tanks in series, using concentration data of tracer in the reactor effluent as a function of time, thus enabling its detailed analysis and comparison with ideal reactor models. With the information from the RTD it becomes possible to design an appropriate reactor model system which reflects the real behavior of the mixture in the tank. The tool was developed in such a way that it is possible to assist in the analysis of RTD data and its characterization parameters from any amount of experimental tracer concentration data originating from pulse-type injection. The software was developed using the Python programming language with the help of available libraries. The graphical interface was created using the Tkinter library, making the tool dynamic and accessible. The numerical integration methods used in the work were implemented with the aid of the Numpy library. The results obtained with the use of the developed tool are positive, ensuring agility and reliability in the characterization and analysis of RTD, providing a descriptive section of the mathematical models used and a brief synopsis of how to operate the software. In addition, if the user enters any data incorrectly, he will be alerted so that can make the correction. The results are obtained efficiently and presented to the user in a concise way.